2019
DOI: 10.1007/s00296-019-04332-6
|View full text |Cite|
|
Sign up to set email alerts
|

Endorsement by Central European experts of the revised ESCEO algorithm for the management of knee osteoarthritis

Abstract: Osteoarthritis (OA) is characterized by deterioration of the joints and associated with considerable pain and disability. OA is a chronic disease that requires intervention with both non-pharmacological and pharmacological treatment modalities and, inevitably, disease progression may necessitate successive treatments throughout the course of the disease. There is increasing data on the shortfalls of current pharmacological treatment of OA, and safety concerns associated with analgesic therapy use in OA arising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
1
14
0
1
Order By: Relevance
“…Therefore, in 2019, a new algorithm [13] was published taking into account the recent evidence on efficacy and safety of medications commonly used for knee OA and the GRADE (Grading of Recommendations Assessment, Development and Evaluation) process was added, to better highlight the evidence used in the algorithm in a transparent and systematic way [14]. Since 2014, the ESCEO algorithm has been well-received worldwide and endorsed by many national societies with a consequent translation, adaptation to the local context, and publication in several countries including China, Russia, Central Europe and Southeast Asia [15][16][17][18][19][20]. For this reason, a working group (WG) was formed between members of the international ESCEO task force (N.V., J.M.K., and J.-Y.R.)…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in 2019, a new algorithm [13] was published taking into account the recent evidence on efficacy and safety of medications commonly used for knee OA and the GRADE (Grading of Recommendations Assessment, Development and Evaluation) process was added, to better highlight the evidence used in the algorithm in a transparent and systematic way [14]. Since 2014, the ESCEO algorithm has been well-received worldwide and endorsed by many national societies with a consequent translation, adaptation to the local context, and publication in several countries including China, Russia, Central Europe and Southeast Asia [15][16][17][18][19][20]. For this reason, a working group (WG) was formed between members of the international ESCEO task force (N.V., J.M.K., and J.-Y.R.)…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, an analysis based on health insurance claims indicated that the prevalence of knee OA was 12.1 % in Germany, in which females were more often affected than males (13.4 vs. 9.7 %) [2]. Across Europe, age-standardized, self-reported, and doctor diagnosed OA ranged from 2.8 % in Romania to 18.3 % in Hungary [3]. Symptomatic knee OA is highly prevalent among people aged over 50 years, affecting more than 250 million people worldwide [4].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the Ultra Micronized Palmitoylethanolamide was found to improve the sleep-awake rhythm in these patients, thus giving the way to an improvement in pain perception and overall health conditions 5 . Other molecules are Group B vitamines and N-Acetyl Carnitine seem to be effectives on neuropathic pain , while Symptomatic slow-acting drugs for osteoarthritis (SYSADOAs), such as glucosamine and chondroitin sulfate, act on nociceptive pain, that is especially related to osteoarthritis 6 .…”
mentioning
confidence: 99%